TAX MORALE, CORPORATE GOVERNANCE, AND AGGRESSIVE TAX PLANNING - Loso Judijanto; Yunia Oktari; Devi Rahnjen Wijayadne (Adisam Publisher, 2026)
The purpose of this study is to examine the connection between aggressive taxation, company governance, and tax morale planning through a literature review approach. Tax morale reflects taxpayers' attitudes and awareness in voluntarily fulfilling their tax obligations, while corporate governance serves as an oversight mechanism in corporate decision-making, including tax planning practices. This study employed a literature review methodology, examining a range of scientific sources, such as books, journals, and pertinent research papers. The findings show that elevated levels of tax morale tend to suppress aggressive tax planning practices due to the increased ethical awareness of tax compliance. On the other hand, the implementation of good corporate governance can reduce aggressive tax avoidance practices through effective oversight and transparency. However, in some cases, weaknesses in corporate governance can be exploited to implement aggressive tax strategies. Therefore, the synergy between improving tax morale and strengthening corporate governance is a crucial factor in minimizing aggressive tax planning practices and supporting sustainable tax compliance.